2022
DOI: 10.12998/wjcc.v10.i33.12221
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of recombinant human brain natriuretic peptide against contrast-induced nephropathy in elderly acute myocardial infarction patients: A randomized controlled trial

Abstract: BACKGROUND Increasing reports have demonstrated that recombinant human brain natriuretic peptide (rhBNP) can improve acute myocardial infarction (AMI) and heart failure. However, whether it can improve renal function and decrease the risk of contrast-induced nephropathy (CIN) in elderly AMI patients is still unclear. AIM To explore the effect of rhBNP on CIN in elderly AMI patients after percutaneous coronary intervention (PCI). METHODS One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…It mainly regulates hemodynamics by activating vascular endothelial protein kinase so as to promote vasodilation. Previous studies have proven that it is effective in treating myocardial infarction and other diseases [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It mainly regulates hemodynamics by activating vascular endothelial protein kinase so as to promote vasodilation. Previous studies have proven that it is effective in treating myocardial infarction and other diseases [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this may be due to rhBNP's ability to relieve peripheral circulation and cardiac load, increase coronary artery blood supply, promote the recovery of myocardial cell function, further increase myocardial contractility, and dilate blood vessels while treating, thereby improving the patient's overall condition. In addition, studies have shown that rhBNP can maintain vascular and renal hemodynamic balance by reducing the secretion of renin and aldosterone, an antagonizing antidiuretic hormone from the posterior pituitary gland, and preserving sodium in the sympathetic nerves (18), which is more conducive to the recovery of patients' hemodynamics.…”
Section: Comparison Of Cardiac Function Biomarkers Before and After T...mentioning
confidence: 99%